MPLS and the evolving Internet architecture. - Li, T. (IEEE Communications magazine)
The Internet architecture has evolved over time, adapting to the needs of its users and incorporating new technology as it has been developed. The introduction of multiprotocol label switching (MPLS) as a part of the Internet forwarding architecture has immediate applications in traffic engineering and virtual private networks. In the longer term, MPLS may affect how traffic transits the Internet and the services that the Internet delivers